Contención química de un puma (Puma concolor) mediante Ketamina-Medetomidina, revertida con Atipamezol, en Tamaulipas, México - Rendon Franco, Emilio; Caso, Arturo; Brousset Hernández-Jáuregui, Dulce Maria (Instituto de Ecología, A.C., 2007)
Chemical restraint of a free-ranging male cougar (Puma concolor) was carried out with Ketamine (90 mg) and Medetomidine (1.2 mg) by an airgun. During the chemical restraint, was necessary to apply additional 75 mg of ketamine. The procedure was reverted with atipamezol. During chemical restraint the animal had excessive salivation and vomit.